Effectiveness of the Riau Islands Province Planning, Research and Development Agency in Carrying out Priority Activities In the Riau Islands Province - Dani Rezki Saputra Siregar (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
This research aims to determine the effectiveness of the Riau Islands Province Planning, Research and Development Agency in carrying out priority activities in the Riau Islands Province. As well as knowing the obstacles that influence the effectiveness of the Riau Islands Province Planning, Research and Development Agency in carrying out priority activities in the Riau Islands Province. This research is descriptive qualitative in nature with data collection techniques in the form of interviews and observations. According to Richard M. Steers, effectiveness is usually used to measure the extent to which a group or organization is effective in achieving a goal. According to Steers (2014:45-48) the essence of organizational effectiveness is, Clarity of Goals, Philosophy, Composition and Structure, Organizational Technology and Organizational Environment. The results of this research are that there are several factors that influence the effectiveness of the Riau Islands Bapelitbang, including limited budget, lack of experts, lack of involvement of local government, community and other stakeholders, lack of availability and quality of accurate and up-to-date data and information, and lack of supervision. and regular and periodic evaluation. The limited budget makes it difficult for the Riau Islands Bapelitbang to meet its operational needs, such as purchasing tools and equipment, implementing training, and improving facilities and infrastructure. Apart from that, the lack of experts is an obstacle in implementing the Riau Islands Bapelitbang's priority activities. Adequate experts are required who have competence in accordance with the needs of Bapelitbang Riau Islands in carrying out priority activities. The involvement of local government, the community and stakeholders Is a very important key factor in supporting and facilitating Bapelitbang Riau Islands activities so that they can run effectively and efficiently. The availability and quality of accurate and up-to-date data and information is an important factor in supporting the implementation of Bapelitbang Riau Islands' priority activities and the need for more regular and periodic monitoring and evaluation is very necessary to measure the effectiveness of Bapelitbang Riau Islands in carrying out priority activities, as well as making necessary repairs and improvements.